Molecular ecology of a shallow water shrimp, Acetes sibogae sibogae Hansen 1919: Evidence for strongly limited gene flow across the western Pacific. (23rd January 2022) - Hardianto, Eko; Fukuchi, Jun; Hanamura, Yukio; Wijayanti, Diah Permata; Sabdono, Agus; Imai, Hideyuki
Abstract: The shallow water shrimp Acetes sibogae sibogae is an ecological and economically important organism in the Asian region. We assessed the genetic diversity and population structure of this species based on samples obtained from eight sites in Japan, the Philippines and Indonesia. Nucleotide sequence analyses were performed based on PCR‐amplified mitochondrial DNA fragments comprising the control region and part of the 12S rRNA gene. In total, 656 bp nucleotide sequences were obtained from 377 individuals. The results show a low haplotype diversity value in shrimp from the Kokuba‐gawa River (0.5) in Japan and intermediate values (0.79–0.99) in other populations. While nucleotide diversity estimates in all sampled localities were lower (0.17%–0.86%) than those reported in other crustaceans, analysis of molecular variance revealed significant genetic differentiation ( p  < .001) among all sites. Furthermore, the mean fixation index estimate was very high ( F ST : 0.27), indicating that dispersal potential among sites was low and gene flow, therefore, was restricted. The mismatch distribution of pairwise differences between haplotypes indicated that A. s. sibogae did not fit a sudden population expansion model. Overall, the present study indicates that wild stocks of A. s. sibogae on Okinawa‐jima Island and the Philippine and Indonesian Archipelagos should be assigned high importance for conservation management of this species because adapted genotypes have significant evolutionary potential during environmental changes. [Correction added on 5th February 2022, after first online publication: Values have been corrected in the Abstract section.]